Model Desain Apotik Hidup bagi Keberlanjutan Pemanfaatan Pengolahan Sampah Organik Rumah Tangga di Desa Ciangsana, Kabupaten Bogor - Silia Yuslim; Etty Indrawati; Dwi Indrawati; Olivia Seanders (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Ciangsana Village, Gunung Putri sub-district, Bogor district has carried out independent waste management. There are two waste banks there, the Cantik waste banks in RW 20 and the Cinta Waste Bank in RW 21. This waste bank has also spurred local communities to process organic kitchen waste independently, but the processing results in the form of compost require more use. Continue to maintain its sustainability, especially in RW 20. The Community Service Program (PkM) majoring in Landscape Architecture coordinate and consult to create a living apothecary design model on the land around Bank Cantik and explain making it and structuring it into a park in activities counseling. The benefits felt from this PKM activity can be seen based on a questionnaire distributed to PKM participants: representatives of the Waste Bank management, PKK women, and RW management (RW heads and secretaries). The results of this PkM show that of all the participants' statements, 96% described that modeling was beneficial for the participants. Still, one participant did not need assistance in applying the design model in the field.